Predictive factors of patient length of stay with multiloculated pleural effusion after medical thoracoscopy: single-center retrospective cohort study - Wiwien Heru Wiyono; Mohamad Fahmi Alatas; Andika Chandra Putra; Erlina Burhan; Amirah Nisrina; Elvan Wiyarta; Gita Fajri Gustya; Muhammad Ilham Dhiya Rakasiwi; Adlina Briliani (BMC Pulmonary Medicine)
Abstract Background Loculated pleural effusion (PE) is a complex condition that often necessitates thoracoscopy due to diagnostic and therapeutic challenges. This study aimed to identify factors influencing the length of stay (LoS) after rigid medical thoracoscopy for loculated PE and assess clinical outcomes, including improvements in lung function. Method This was a retrospective cohort study conducted at St. Carolus Hospital, Jakarta, from October 2011 to December 2020. The inclusion criteria were patients with multiloculated pleural effusion requiring thoracoscopy and available preoperative and postoperative FEV1 and FVC results, while the exclusion criteria included patients with contraindications for thoracoscopy and missing surgery duration, LoS, or pathological data. Pearson and Spearman correlation analyses and correlation tests were used to assess the relationships between variables, with linear regression performed to identify significant predictors. Results A total of 58 patients with multiloculated pleural effusion who underwent rigid thoracoscopy were enrolled. Significant improvements were observed in both the predicted FEV1 and FVC (p < 0.001) between the preoperative and postoperative measurements. Through multivariate analysis, we discovered a significant negative correlation between preoperative predicted FEV1 (β = -0.09, p = 0.036) and LoS. Conversely, there was a positive correlation between the duration of surgery and LoS (β = 0.088, p < 0.001), with a constant value of 6.852. Using the β coefficient and constant found in multivariate analysis, an equation was obtained to predict patient LoS using parameters of preoperative predicted FEV1 and duration of surgery. Conclusion Preoperative predicted FEV1 and the duration of the procedure are predictive factors for LoS in multiloculated PE patients undergoing rigid thoracoscopy. Clinical trial numbers Not applicable.